Studi Korelasional Spiritualitas Dan Burnout Syndrome Perawat Ruang Kritis Selama Pandemi Covid-19 - Rudiyanto; Purnamasari, Andita; Dwi Prasetyawan, Riyan; Rosuli, Ahmad; Waliyyun Arifuddin, Yusuf; Munif, Badrul (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
The COVID-19 pandemic has put extraordinary pressure on medical personnel, especially nurses who work in critical wards. They are faced with high health-related risks as well as constant psychological stress. This study aims to investigate the relationship between the level of spirituality of nurses and the level of burnout syndrome they experience during the pandemic. This research was conducted using a survey method and data collection through questionnaires (SWBS (Spiritual Well Being Scale) and MBI-HSS (Maslach Burnout Inventory Human Service Survey)) which were given to 55 nurses who work in critical rooms selected using total sampling techniques. Research data was analyzed using Chi-square with Fisher's Exact Test. The research results showed that almost all nurses had a high level of spirituality (85.5%) and the majority of nurses did not experience burnout syndrome (60.0%). The calculated statistical value obtained a sig (2-tiled) value of 0.007 (p<0.05) meaning that there is a significant relationship between the level of spirituality of nurses and the level of burnout syndrome they experience. Nurses with higher levels of spirituality tend to experience lower levels of burnout. This indicates that aspects of spirituality, such as strong beliefs and regular spiritual practices, act as protective factors in reducing the risk of burnout syndrome. Apart from that, it is also important to include a holistic approach that pays attention to spiritual aspects in care and support for nurses during pandemics and other critical situations.